A study on organizational commitment and job satisfaction among employees at selected government agencies in Kelantan / Atiela Amran ...[et al.] - Amran, Atiela; Mohd Firdaus Kozako, Intan Nurul ‘Ain; Aminuddin, Azwan Shah; Hanitahaiza, Hairuddin; Ibhrahim, Zakaria (Universiti Teknologi MARA, 2021)
Organizational commitment is one of the main topics discussed in today’s working environment. Most of the scholar agreed that to make the employees highly commit to the organization, employees must have satisfaction with their work. Further study related to this area is still needed to identify the most important criteria to the specific industries. Hence, this study conducted a non-experimental study in which researchers investigated and analysed the relationship between organizational commitment and job satisfaction, in which focuses on continuance, normative, and effective commitment. There are 140 valid responses collected from three government agencies in Tanah Merah, Kelantan. Regression analysis were used for this study to identify the relationship between two variables. The result of descriptive statistics showed that continuance commitment represents the highest mean score for this study. Meanwhile, organizational commitment has a moderate, positive, and significant relationship towards job satisfaction (r=598, p* 0.01.) It can be concluded that most of the respondents used to have effective commitment towards the organization where they remain members and part of the organization. The researchers also suggest several recommendations for future research regarding this study.